The Treaty of Waitangi as an Exercise of Māori Constituent Power - Orsman, Jessica (Victoria University of Wellington Law Review, 2012)
This article analyses the Treaty of Waitangi in light of Carl Schmitt's concept of constituent power – the idea that in a democracy the people hold the power to make fundamental political decisions to determine their form of political existence. It finds that in 1840, Māori, as the holders of constituent power, made a fundamental political decision to share authority between themselves and the Crown. This fundamental political decision is a key element of the New Zealand constitution; limiting potential constitutional changes that would override the substance of the decision, and requiring changes to the current legal framework in order to comply with the decision to share authority. This article focuses solely on the conservative implications of characterising the Treaty as a fundamental political decision. It concludes that only a further exercise of constituent power by Māori can legitimately override or significantly change the fundamental political decision in the Treaty.